Clinical Phenotypes of Patients with Neovascular Age-Related Macular Degeneration and Poor Response to Aflibercept Treatment - V. G. Likhvantseva; A. S. Gevorgyan; S. G. Kapkova; E. Yu. Nekrasova (Oftalʹmologiâ, 2022)
The purpose: to identify and describe the clinical phenotypes of patients depending on their response to treatment with Aflibercept.Material and methods. The study had a prospective cohort design, including 92 eyes (n = 84) with a newly diagnosed diagnosis of nAMD and signs of disease activity. According to the OCT, the activity and type of macular neovascularization (MNV) were verified. Disease activity was monitored by central retinal thickness (CRT), the presence of subretinal and intraretinal fluid (SRF, IRF), and pigment epithelial detachment (PED). Eyes showing fresh hemorrhage ophthalmoscopically, OCT signs of SRF, IRC or sub-RPE, and dye leakage on the FAG were classified as having active nVMD. Treated with intravitreal injections (IVI) of Aflibercept 40 mg/ml in the “treat and extend” mode. The group with an unsatisfactory response to treatment was divided into 5 subgroups: true non-responders (without changes in activity throughout the course of treatment); partial nonrespondents (minimal regression of SRF and/or IRF) during treatment; dependent on anti-VEGF (complete regression on the background of injections, relapse after 4 weeks (increase in SRF/IRF, sub-RPE fluid, PED size); progression of anatomical changes, with exudation or hemorrhage, despite treatment; decreased response to treatment over time. Studied differences in baseline characteristics between the eyes among respondents and non-respondents and in five subgroups of incomplete respondents.Results. In the OCT characteristic, 45.5 % of eyes with tachyphylaxis showed normal CRT, lack of SRF (90.9 %) and IRF (90.9 %), high prevalence of fibrovascular PED (90.9 %); 90.0 % of the eyes showed type 1 MNV. In the subgroup of non-respondents with anatomical deterioration, type 2 and 3 of MNV were more often present (p = 0.00001) and fibrovascular-hemorrhagic PED was present in every sixth eye. Half (51.2 %) of the VEGF-dependent eyes (p = 0.0139) had the phenotype SRF+ and IRF- (91.3 % vs. 57.9 %, p = 0.0123), dominated by the OCT phenotype: SRF+/IRF-, as well as type 1 and 2 of MNV (91.3 % and 8.7 %, respectively). The eyes are partially non-respondent in 32 % had normal CRT, in 40 % of the eyes SRF+, in 24 % of IRF+, different types of PED, 1 and 3 types of MNV were present.Conclusion. The presented descriptions of clinical phenotypes of eyes with nVMD depending on their response to treatment with Aflibercept may be useful in predicting the response to treatment.